Mechanical recycling of tags and labels residues using sugarcane bagasse ash - Mantovani,Guilherme Augusto (2017)
Abstract In this study, an alternative method for recycling residues of labels and stickers (parings) containing biaxically oriented polypropylene (BOPP) and polyurethane-based glue was discussed. The recycling of this type of material is complicated, once the separation and the milling processes are difficult to be accomplished, due to the presence of a large amount of glue. In this study, sugarcane bagasse ash was used to enable the milling process of stickers residues. Composites were prepared with post-consumer polypropylene extrusion with different polypropylene/parings ash ratio. These materials were analyzed by tensile, three point flexural, hardness, density, water absorption, Izod impact tests, thermogravimetric analysis, environmental exposure and scanning electron microscopy. Addition of sticker residues/ash to the polypropylene matrix makes the material more rigid and does not affect significantly thermal and degradation properties. Thus, the recycling process proposed in this paper is environmentally and economically viable.